Oleogels for development of health-promoting food products - Artur J. Martins; Antonio A. Vicente; Lorenzo M. Pastrana; Miguel A. Cerqueira (Food Science and Human Wellness)
Metabolic health and the maintenance of good levels of triglycerides, high-density lipoprotein cholesterol, blood pressure and glucose levels are concerns that can greatly impact human quality of life. Health-driven consumers’ demands, together with technological innovations, have led to a diversification of the food industry. The fostering of off-the-shelf available and affordable healthy food products is necessary, as detrimental effects on human health from the ingestion of saturated fat sources urge the efforts to find alternatives. Oleogels can be tailored using specific triglycerides and oleogelators, that can be selected to yield targeted fatty acids, reduce higher levels of cholesterol with competing binding-molecules (e.g. phytosterols), reduce saturated fat content, lessen appetite (e.g. modelling the shape of foods) or carry exclusive bioactive compounds to be absorbed in the digestive tract. Oleogels are foreseen as an important technological advance in food science due to their versatility, easy processing and affordability. This review explored the strategies in place to develop and produce oleogels, foreseeing their introduction in foods and how they might represent an important source of functionality through the use of healthy molecules. It also explored how oleogels can act on the human overall metabolic health if they are used in human diet. Keywords: Oleogel, Vagal pathway, Nutrition, Fatty acids, Metabolism, Gut-brain axis